Peran Tiktok Dalam Membentuk Loyalitas Merek Dan Perilaku Konsumen Generasi Z - Stevie Angel Feronica Makatita; Iswadi Iswadi (Journal of Innovative and Creativity, 2025)
This study aims to examine the role of TikTok as a platform in shaping brand loyalty and influencing the consumer behavior of Generation Z. Using a descriptive qualitative approach and exploratory case study method, the research analyzes communication strategies of three popular brands—Scarlett Whitening, Tokopedia, and Emina—actively utilizing TikTok. Data collection involved digital content observation, in-depth interviews with ten Generation Z informants, and literature review. The findings reveal that authentic, interactive, and community-based content such as hashtag challenges, user-generated content, and live streaming are effective in fostering emotional attachment and long-term brand loyalty. TikTok also serves as a key source of product information and enables the formation of digital communities that strengthen consumer identity. The study affirms that TikTok has evolved from an entertainment app into a strategic communication channel crucial for engaging and retaining the digital-native youth audience.